Effects of Dietary Coated Folic Acid and Folic Acid Addition on Lactation Performance, Rumen Fermentation, and Hepatic Lipid Content in Early Lactation Dairy Cows - Nan Sun; Songming Zou; Jiaxin Feng; Gang Guo; Qiang Liu; Yawei Zhang; Lei Chen; Wenjie Huo; Cong Wang (Animals)
This study evaluated the influences of coated folic acid (CFA) and folic acid (FA) on lactation performance, apparent digestibility, rumen volatile fatty acid (VFA) production, blood metabolism, and hepatic lipid content in cows. A total of 140 Holstein cows were allocated to seven groups in a randomized block design. Cows in the control received no addition, those in the in low CFA (LCFA), medium CFA (MCFA), and high CFA (HCFA) groups received CFA at 135, 270, and 405 mg FA/d, and those in the low FA (LFA), medium FA (MFA), and high FA (HFA) groups received FA at 135, 270, and 405 mg/d. The experiment began 5 weeks before calving to 6 weeks after calving. When increasing the level of CFA, the fat-corrected milk (FCM), fat and protein yields, de novo fatty acid content, and feed efficiency increased linearly. A linear increase was observed for nutrient digestibility and ruminal total VFAs. The blood total protein, albumin, superoxide dismutase, glutathione peroxidase, and folate increased linearly, but blood non-esterified fatty acids and β-hydroxybutyric acid and hepatic lipids decreased linearly. When increasing the level of FA, the FCM and milk fat yields increased linearly, but the rumen total VFA increased quadratically. Compared with MFA, cows receiving MCFA had a greater milk yield and lower hepatic lipids. Overall, the addition of CFA increased the milk yield and decreased the hepatic lipid content in cows.